PENGARUH PENGAWASAN FUNGSIONAL, PENYAJIAN LAPORAN KEUANGAN DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PUBLIK (Studi Empiris pada SKPD Pemerintah Kabupaten Siak) - Shella Lolita diti Aprilia; Nur Azlina; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of the functional supervision, financial report presentation and financial report accessibility on public accountability. Population and sample in this research was in the SKPD Siak. Collecting data using primary data, the questionnaire using purposive sampling technique. The hypotheses then tested is multiple linear regression analysis by using SPSS version 21.0. The results of this study were 1)Functional supervision effect on public accountability. 2) Financial report presentation effect on public accountability. 3) Financial report accessibility effect on public accountability.The influnce of Functional supervision, Financial report presentation, and Financial report accessibility are 78,2% while the remaining 21,8 % is influenced by other variables.Keywords:Public Accountability, Functional Supervision, Financial Report Presentation, Financial Report Accessibility.